PENGARUH TRANSPARANSI, AKUNTABILITAS, PARTISIPASI MASYARAKAT, DAN KOMPETENSI APARAT DESA TERHADAP PENGELOLAAN DANA DESA - Maryono; Aulia Rakhma Larasati Putri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of transparency, accountability, community participation, and competence of village officials on the management of village funds in villages in Wanasari District, Brebes Regency. This type of research is quantitative research using descriptive methods. The sampling technique used purposive sampling with the number of respondents as many as 7 people per village, so that the total respondents were 140 people. The data analysis method used is multiple linear regression analysis using the SPSS version 21 program. Based on the results of the research conducted, it shows that transparency, accountability, community participation, and the competence of village officials simultaneously have a significant effect on the management of village funds. While partially, transparency has no significant effect on the management of village funds. Accountability has a significant positive effect on the management of village funds. Community participation has a significant positive effect on the management of village funds, and the competence of village officials has a significant positive effect on the management of village funds.